Transformer-ethosomes with palmitoyl pentapeptide for improved transdermal delivery - Kim, Joo Eun; Oh, Ga Hui; Jang, Gi Hyun; Kim, Yu Mi; Park, Young Joon (Journal of Drug Delivery Science and Technology, 2019)
The aim of this study was to develop flexible lipid carriers loaded with palmitoyl pentapeptide (PPP) for improved transdermal delivery. Transformer-ethosomes (TESs), composed of phosphatidylcholine and fatty acids, were prepared by a modified extrusion method. The physicochemical characteristics of PPP-entrapped TESs (PPP-TESs) indicated that they had a mean diameter of <150 nm, a homogeneous particle population, a net positive surface charge, and an encapsulation efficiency (EE) of >97%. Differential scanning calorimetry (DSC) thermograms showed that incorporation of capric acid (CA) and myristic acid (MA) into the lipid bilayers altered their transition temperature and improved flexibility when compared with liposomes and ethosomes (ESs). The flexibility values of TESs containing CA or MA were inversely proportional to the transition temperature of the formulations. The skin permeation of PPP-TESs through either an artificial membrane or human cadaver skin was much higher than that observed with a PPP solution, PPP-liposomes, and PPP– ESs. Moreover, the collected receptor fluid and vertically sliced human skin of rhodamine-6G (R6G)-loaded TES-MA were analyzed by confocal laser scanning microscopy (CLSM) to assess the accumulation of fluorescence in the skin and skin penetration. As a result, TES may be a promising candidate for the transdermal delivery of PPP as well as other drugs.
Keywords: Flexible lipid carrier; Palmitoyl pentapeptide; Skin penetration; Skin permeation; Transformer-ethosomes